Temporal and spatial variation of inversion polymorphism in two natural populations of Drosophila buzzatii. - Fernandez Iriarte, P.J.; Levy, E.; Devincenzi, D.; Rodriguez, C.; Fanara, J.J.; Hasson, E. (Hereditas, 1999)
The inversion polymorphism of the cactophilic fly Drosophila buzzatii was studied in two natural populations. We assessed the temporal changes and microspatial population structure. We observed a significant increase in the frequency of arrangement 2J at the expense of 2ST in both populations. These gene arrangements appear to affect the life-history of flies differently. Environmental heterogeneity explains the karyotype coexistence in nature. The analysis of population structure showed that differentiation of inversion frequencies among individual breeding sites, the rotting clacodes of Opuntia vulgaris, was highly significant. The karyotypic frequencies did not depart significantly from Hardy-Weinberg expectations, neither in individual rots nor in the total population. These results suggest that the observed population structure can be easily accounted by random genetic drift.